Aerial survey of wildfowl in the Highlands of Northern Scotland in the spring of 1959 - Eltringham, S K; Boyd, H (Wildfowl, 1960)
The north of Scotland is the home of the remnants of the indigenous British population of Greylag Geese and of a variety of breeding ducks about which there is little reliable or recent information. Since the country has a comparatively small human population and includes large tracts which are difficult of access, it seemed likely that observations from an aircraft would provide an economical means of studying the distribution of wildfowl in the north. The area to be explored comprised the mainland and inshore islands north of a line from Loch Carron in the west to Iverness in the east. The objects of the survey were two. First, to make a census of Greylags by visiting all the lochs and lochans known to have been used as breeding places within recent years, and as many other likely-seeming places as possible. Second, to obtain a detailed record of the distribution of all species of ducks breeding within the region, paying particular attention to the remoter areas.